Linear lupus panniculitis of scalp: a case report from north-east India - Thokchom, Nandakishore; Salam, Erika; Bhattacharjee, Nandita; Kongbam, Linda (International Journal of Research in Dermatology, 2021)
Lupus panniculitis of scalp is an uncommon manifestation of lupus erythematosus, which presents as non-scarring linear, arched, or annular alopecia along the lines of Blaschko. A 7 year old child presented with localised linear non-scarring alopecia on scalp. Examination revealed a single linear alopecic patch on the left parietal scalp. There were no associated systemic complaints. Skin biopsy showed atrophic lining epithelium, diffuse and nodular lymphocytic and plasma cells infiltrates in the superficial and deep dermis, lobular inflammatory infiltration of lymphocytes, histiocytes and plasma cells, with minimal involvement of septa in the subcutaneous tissue. Antinuclear Antibody (ANA) and anti-ds DNA tests were negative. Patient responded well with regrowth of terminal hair within 3 weeks to a combination treatment of hydroxychloroquine, topical and intralesional steroids, and topical calcineurin inhibitor. Linear lupus panniculitis of scalp should be considered in cases of patterned, non-scarring alopecia. Regular follow-up is also essential due to the possibility of recurrence and development of systemic lupus erythematosus.